Telephony's next act. - Mockapetris, P.V (IEEE spectrum)
This paper discusses the impending merger of traditional telephone networks and the Internet via a new technology, called voice over Internet Protocol (VoIP). A key issue that must be addressed is how to merge the respective databases of the two communication networks. With a new type of data record, called ENUM (electronic number), the legacy information of both telephony and the Internet can be accommodated and allow a phone number to be converted to an Internet address. DNS capabilities, however, first need to be strengthened to ensure they can meet the demands of ENUM and other new network technologies.